Industrial characteristics, production milieu and regional innovation: A comparison of Israel and German industrial plants - Amnon Frenkel; Daniel Shefer; Knut Koschatzky; Gunter Walter (European Regional Science Association (ERSA), 1998)
In recent years, we have been witnessing a growing number of researchers whose objective is to gain a better understanding of the variation in the rate of spatial innovation of different industrial plants. Only a very small number of studies, however, have investigated the similarity and dissimilarity of spatial innovation between countries. This study attempts to fill this gap. It reports the results of a larger study carried out jointly by a team of researchers from Germany and Israel. In Germany, the study focused on the State of Baden Wurttemberg, and in Israel on the Northern District. Altogether in both countries, more than 400 industrial plants, belonging to the fastest-growing industrial branches (Electronics, Metals and Plastics) were included in the study. The use of simple statistical models, augmented by multi-variable Logit Models, enabled us to point out the similarity and dissimilarity in spatial innovation patterns between the two countries. The results further support the hypothesis that expenditure on R&D is a good surrogate for the probability of the firm to innovate, regardless of the industrial branch to which the plant belongs. In general, we can conclude that there exists a strong similarity in the frequency of industrial innovation in both countries; i.e., the rate of innovation in their hi-tech industries is significantly higher than in their traditional industries. On the other hand, the pattern of spatial variations in the rate of innovation in Israel is much more pronounced and visible compared to Germany.
Keywords: 330